A longitudinal bottom-up analysis of staff travel patterns (2018–2023) at a research-intensive university hospital - N. Gebhardt; O. A. Kern; L. Schwaab; H.-C. Friederich; C. Nikendei (Discover Sustainability)
Abstract University hospitals are part of the health care system, as well as academia. The carbon footprint of staff travel, quantified as greenhouse gas (GHG) emissions, is significantly enlarged by academic air travel in these facilities. Both as an academic institution and as a health care provider, they have a special obligation to mitigate their GHG emissions. Yet, there exist no data-driven analyses of staff travel at university hospitals, nor have quantitative evaluations of mitigation measures been published so far. Methods. GHG emissions were calculated bottom-up from administrative data for all travel activities in 2018–2023 at a large university hospital active in international research. In a second step, we calculated net reductions in GHG emissions for potential reduction measures. Results. In total, 26,833 trips were analyzed. Due to an overall decrease in traveling activities, GHG emissions in 2023 have decreased to 63% of the pre-COVID levels in 2019. Most trips were undertaken by train (65.8%), but 94.8% of GHG emissions originated from air travel. On average, medical professors emitted 24 times as much GHG as regular physicians per person, and 10 times as much as scientific research personnel. Reducing intercontinental flights by 50% would save up to 44% of net GHG emissions, reducing trips by plane with less than two overnight stays by 50% would save 19%, and reducing flights by senior staff by 50% would save 14%. Conclusion. Academic air travel, the internationalization of research activities, and extensive travel behavior by senior staff should be critically assessed. Doctors and researchers are considered the most trustworthy professions worldwide and could lead transformations towards sustainable travel behavior.